Wind Reversals During Morning and Evening Transitions in a Small Valley - Rui Zhang (20177106) (2025)
The observation data includes three datasets recorded from an observation tower in Innisfree Village, located at the foot of the Blue Ridge Mountains in Virginia, USA. Covering the entire year of 2020 and 2021 with measurements taken every minute, the datasets capture a range of atmospheric and environmental variables. The files “onset_2020” and "onset_2021" record wind speed, gust speed, wind direction, temperature, relative humidity, solar radiation, atmospheric pressure, voltage, current, and rainfall; The files “Rad_Means_2020” and "Rad_Means_2021" provide incoming and outgoing shortwave radiation, and incoming and outgoing longwave radiation; The files “TempRH_Means_2020” and "TempRH_Means_2021" include readings from multiple sensors, including temperature at different heights and relative humidity, as well as target and detector temperatures and voltage. The file “20210521_d03” is the output of domain 3 simulated by WRF on May 21, 2021. The Weather Research and Forecasting (WRF) model (Version 4.4.2) is used in this study. The outmost domain covers an area of 500×500 km with a horizontal grid spacing of 3 km. The horizontal grid spacing decreases to 1 km for d02 and 0.33 km for d03, while d02 and d03 cover an area of 100×100 km and 10×10 km, respectively. There are 56 vertical levels for all the domains with 17 layers below 1.5 km, and the model top is at 52-hPa. The model is driven by NCEP GDAS Final Analysis Data with a horizontal resolution of 0.25°×0.25°. The simulation is initialized at 00:00 UTC of May 21, 2021 (19:00 EST, May 20, 2021) and run for 30 hours until 06:00 UTC of May 22, 2021 (01:00 EST, May 22, 2021). Model output data were saved at 1-minute intervals.